Effects of Calcium and Annatto Tocotrienol Supplementation on Bone Loss Induced by Pantoprazole in Male Rats - Chin KY; Thong BKS; Kamalulloh RF; Mohamad NV; Wong SK; Mohd Arlamsyah A; Triliana R; Soelaiman IN (Dove Medical Press, 2020)
Kok-Yong Chin,1 Benjamin Ka Seng Thong,1 Rhivaldy Faahim Kamalulloh,2 Nur Vaizura Mohamad,1 Sok Kuan Wong,1 Azlan Mohd Arlamsyah,1 Rahma Triliana,2 Ima Nirwana Soelaiman1 1Department of Pharmacology, Faculty of Medicine, Universiti Kebangsaan Malaysia, Cheras 56000, Kuala Lumpur, Malaysia; 2Faculty of Medicine, Islamic University of Malang, Kota Malang 65144, Malang, IndonesiaCorrespondence: Kok-Yong ChinDepartment of Pharmacology, Faculty of Medicine, Universiti Kebangsaan Malaysia, Jalan Yaacob Latif, Bandar Tun Razak, Cheras 56000, Kuala Lumpur, MalaysiaTel +603-9145 9573Fax +603-9145 9547Email chinkokyong@ppukm.ukm.edu.myPurpose: Prolonged use of proton pump inhibitors may cause bone loss, and limited therapeutic agents are available to prevent this skeletal side effect. The combination of annatto tocotrienol, a bone anabolic agent, with calcium presents a novel strategy to prevent bone loss caused by proton pump inhibitors. This study aims to compare the effects of calcium alone and in combination with annatto tocotrienol or vitamin D3 (Caltrate Plus) in preventing bone loss caused by pantoprazole.Methods: Three-month-old Sprague Dawley male rats (n=30) were randomised into five groups (n=6/group). Bone loss was induced by pantoprazole (3 mg/kg p.o.) in four groups, and they were treated concurrently with either calcium carbonate (77 mg p.o.), calcium carbonate (77 mg p.o.) plus annatto tocotrienol (60 mg/kg p.o.) or Caltrate Plus (31 mg p.o.) for 60 days. The rats were euthanised at the end of the experiment, and their femurs were harvested for X-ray micro-computed tomography, bone cellular histomorphometry and bone mechanical strength analysis.Results: Pantoprazole caused significant deterioration of trabecular bone microstructures but did not affect other skeletal indices. Calcium supplementation with or without annatto tocotrienol prevented the deterioration of trabecular microstructures at the femur but did not improve other skeletal indices. Annatto tocotrienol did not enhance the skeletal actions of calcium, whereas Caltrate Plus did not affect the bone health indices in these rats.Conclusion: Calcium supplementation per se can prevent the deterioration of bone trabecular microstructures in rats receiving long-term treatment of pantoprazole.Keywords: osteoblast, osteoclast, osteopaenia, osteoporosis, proton pump inhibitor, vitamin E